2019
DOI: 10.18510/hssr.2019.7663
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Work Behavior and Innovative Work Behavior: Moderating Effect of Job Characteristics

Abstract: Purpose of study: This study examined the usefulness of job characteristics as a technique designed to enhance the effect of proactive behavior and innovate work behavior. Methodology: A field study was conducted with a randomly selected sample of company 145 supervisors of Sharia Bank at West Java Indonesia. This research was used as a quantitative approach to analyze and answer all research questions. And then, hypotheses for direct and moderator effects are tested using hierarchical regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
4
21
0
1
Order By: Relevance
“…(7) There is a positive and significant effect of PP on PWB mediated by RBSE because of the significant direct effect of PP on RBSE and RBSE on PWB with a positive value of 0.464. This is consistent with the findings by Nurjaman et al (2019), who discovered that PWB is important for organizations since it is likely to enhance present work situations and open up new chances. The State Detention Center (RUTAN) in Indonesia need something comparable.…”
Section: Discussionsupporting
confidence: 92%
“…(7) There is a positive and significant effect of PP on PWB mediated by RBSE because of the significant direct effect of PP on RBSE and RBSE on PWB with a positive value of 0.464. This is consistent with the findings by Nurjaman et al (2019), who discovered that PWB is important for organizations since it is likely to enhance present work situations and open up new chances. The State Detention Center (RUTAN) in Indonesia need something comparable.…”
Section: Discussionsupporting
confidence: 92%
“…Employees’ proactive behaviors at work are vital for innovation in organizations [ 1 ]. Previous studies have shown that leadership plays an important role in facilitating employees’ proactive behaviors [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aydın & Tuzun (2019) highlighted the fact that the ability of workers to retain membership in an organization would also increase as effort-outcome expectations increase due to POS. Individuals with high POS will also be less inclined to explore alternative possibilities (Nurjaman, Marta & Eliyana, 2019). Eisenberger (2016) views perceived organizational support as consisting employees' welfare and employee's opinions and goals.…”
Section: Perceived Organisational Supportmentioning
confidence: 99%